2003
DOI: 10.1088/0305-4470/36/23/317
|View full text |Cite
|
Sign up to set email alerts
|

New exact solutions for polynomial oscillators in large dimensions

Abstract: A new type of exact solvability is reported. Schrödinger equation is considered in a very large spatial dimension D ≫ 1 and its central polynomial potential is allowed to depend on "many" (= 2q) coupling constants. In a search for its bound states possessing an exact and elementary wave functions ψ (proportional to a harmonicoscillator-like polynomial of a freely varying, i.e., not just small, degree N), the "solvability conditions" are known to form a complicated nonlinear set which requires a purely numerica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2005
2005
2007
2007

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 47 publications
0
21
0
Order By: Relevance
“…During our study we felt particularly motivated by the technical difficulties arising in connection with the explicit construction of the quartic QES charges. Although, implicitly, they are defined by the coupled pair of the Magyari's polynomial algebraic equations for two unknowns, their practical determination must usually rely upon the computerized, Gröbner-basis-based algebraic manipulation techniques and numerical root-searching [26]. In addition, it is quite unpleasant that the complexity of the latter algorithm grows fairly quickly with the growth of the degree N of the polynomial wave functions as well as with the growth of the angular momentum ℓ.…”
Section: Discussionmentioning
confidence: 99%
“…During our study we felt particularly motivated by the technical difficulties arising in connection with the explicit construction of the quartic QES charges. Although, implicitly, they are defined by the coupled pair of the Magyari's polynomial algebraic equations for two unknowns, their practical determination must usually rely upon the computerized, Gröbner-basis-based algebraic manipulation techniques and numerical root-searching [26]. In addition, it is quite unpleasant that the complexity of the latter algorithm grows fairly quickly with the growth of the degree N of the polynomial wave functions as well as with the growth of the angular momentum ℓ.…”
Section: Discussionmentioning
confidence: 99%
“…is only exceptionally tractable non-numerically at q > 2 [28]. We were still able to recollect a few explicit formulae for q = 2 [5].…”
Section: The Magyari's Family Of Quasi-exact Toboggansmentioning
confidence: 96%
“…These kinds of potentials have drawn attention to the study of P T -symmetry and pseudo-harmonicity of the Hamiltonian [21,22].…”
Section: Non-singular Potentialmentioning
confidence: 99%
“…In a recent work, Gönöul et al [20] have shown that two kinds of potentials as mentioned above can be linked together in N -dimensional space. Nonsingular (polynomial) potentials are also very much fascinating nowadays because of their mathematical beauty like P T symmetry [21] and their application in different branches of physics [22]. Therefore, it will be very much interesting to develop a unified approach for constructing QES potentials of singular and non-singular type.…”
Section: Introductionmentioning
confidence: 99%